KAJIAN TATA LETAK PRODUK SKINCARE LOKAL PADA TAMPILAN ANTARMUKA SAAT LIVE STREAMING - Az Zahra, Maysitha Fitri; Anggraeni, Dinar Safa; Al Khaliq, Barkah (Narada : Jurnal Desain dan Seni, 2024)
Selling lokal skincare products via online platforms, especially via live streaming, has challenges in optimal display arrangements on the user interface. Products are often difficult to see clearly, reducing audience appeal even if they are interesting. This journal aims to explore the arrangement of lokal skin care products online in the marketplace, focusing on determining the best distance between the camera and the product and the optimal distance between cameras to ensure maximum viewing. The research results show that the distance between the camera and the product should not be too far, preferably not exceeding 1 meter, especially when using a 1x zoom lens. The practical implications of this research can help lokal skincare sellers and marketers improve the quality of their product presentations virtually, thereby increasing the attractiveness and trust of potential customers based on layout of the user interface display during live streaming.